1999
DOI: 10.1007/bf02375998
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of LiNi1−yCoyO2 (0≤y≤1) synthesized by wet chemistry via malic acid-assisted technique

Abstract: Abstract.We have synthesized LiNil.yCoyO 2 powders by a sol-gel method using malic acid as a chelating agent. The dependence of physico-chemical properties of the powders (crystallinity, lattice constants, grain size) has been investigated by changing the malic acid quantity and the calcination temperature for the different LiNil.yCOyO 2 oxides in the composition range 0 < y < 1. Structural studies show that a layered single phase was obtained for the y values 0.2 < y < 1.0. The local cationic environment has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The shape of the charge-discharge curves shows a good reversibility even during the first cycle. In the composition domain 1.0 > x > 0.4, the shape of voltage charge profiles of the Li//LixCoO2 cell is almost similar to that recorded on high-temperature grown materials [50].…”
Section: Sol-gel Methodsupporting
confidence: 52%
“…The shape of the charge-discharge curves shows a good reversibility even during the first cycle. In the composition domain 1.0 > x > 0.4, the shape of voltage charge profiles of the Li//LixCoO2 cell is almost similar to that recorded on high-temperature grown materials [50].…”
Section: Sol-gel Methodsupporting
confidence: 52%
“…The homogenous mixture of the powders were packed in a shallow ceramic boat and heat treated at 450°C (melting point of LiOH) for 8 h under a flow of oxygen. Lithium cobaltate powders were also synthesized by wet chemistry method according to the sol-gel procedure reported elsewhere [6] and [7]. Pulsed laser deposited (PLD) LiCoO 2 films were grown onto silicon wafers from targets which were a mixture of LiCoO 2 powder and variable amounts of Li 2 O additive (0≤z≤15%).…”
Section: Synthesis and Structure Of Cathode Materialsmentioning
confidence: 99%
“…Recent studies on LiCOl_yNiyO 2 cathode materials have shown that their electrochemical properties are sensitive to the structure, composition and morphology of the powders [9][10][11][12]. Particles obtained in the nanometer scale with homogeneous distribution of grain size favor the lithium-ion diffusion and improve the intercalation-deintercalation.…”
Section: Introductionmentioning
confidence: 97%